Frederick Herzberg theory of motivation as applied by Mega Paint and Coating Corporation manufacturing in Camomot, Binangonan, Rizal, calendar year 2025 - A; Babia, Vanessa Jean A.; Delmo, Sherlyn Mae P.; Esguerra, Ma. Jaqueline S. (2025)
This study examined the perceptions of employees at Mega Paint and Coating Corporation Manufacturing in Macamot, Binangonan, Rizal, using Frederick Herberg's Two-Factor Theory of Motivation as its framework. The respondents' demographic profile revealed a workforce where the largest segment was aged 21-30 years old, predominantly male, largely single, and defined by a high concentration of college graduates. In terms of employment characteristics. the largest portion of respondents had less than one year of service and held regular employment status. Findings indicated that both motivation factors (achievement, recognition, and personal growth) and hygiene factors (salary, job security, fringe benefits, and working conditions) were generally perceived as "Always Practiced." Recognition and achievement were highly valued, while opportunities for promotion and proactive feedback were less consistently experienced. Hygiene factors, particularly salary and fringe benefits, were also positively viewed, though some aspects, such as merit-based increases and long-term financial stability, were perceived as less consistent. Statistical analysis revealed significant differences in perceptions across age. sex, educational attainment, length of service, and income levels, suggesting that demographic and employment-related factors influence how employees experience motivation and job satisfaction. Notably, no significant differences were observed in certain areas such as job security and working conditions, which were perceived more consistently across groups. Despite these positive ratings, key challenges emerged. The most pressing issues were workplace negativity and disrespect among colleagues, followed by feelings of being undervalued or unsupported by management. Concerns abou financial stability and job security were also noted, while less frequent issue: included inadequate compensation, limited opportunities for advancement, an excessive work pressure. The study concluded that employees at Mega Paint and Coating Corporation generally perceived both motivation and hygiene factors as "Always Practiced," indicating the successful establishment of a positive work environment consistent with Herzberg's theory. While high ratings were observed across critical factors like achievement, recognition, job security, and working conditions, analysis revealed that employee perceptions varied significantly across demographic groups (including age, education, and tenure), with salary, recognition, and job security being the areas demonstrating the most substantial differences. Critically, the research identified specific workplace challenges, including a high level of negativity and disrespect among colleagues, feelings of being undervalued by management, and limited avenues for professional growth, all of which pose a threat to long-term motivation. Therefore, the company may institutionalize high-scoring intrinsic factors like achievement and personal growth while treating the pervasive negativity and disrespect as a priority hygiene failure by implementing a mandatory Code of Conduct Training focused on professional ethics. Management may also adopt more tailored and equitable motivational strategies across the workforce and consider implementing the researcher's proposed employee motivation model framework to improve overall engagement and retention. Overall, the study highlights the importance of maintaining strong recognition and motivational systems while addressing interpersonal challenges and ensuring equitable opportunities for growth, compensation, and long-term stability. These findings provide critical insights for developing strategies that strengthen employee satisfaction and productivity in line with Herzberg's theory.
Undergraduate Thesis
Includes bibliographical references